APPEARANCE AND FUNCTION OF ENDOGENOUS PEROXIDASE IN FETAL RAT THYROID - Strum, Judy M. (The Rockefeller University Press, 1971)
Iodination within the thyroid follicle is intimately associated with a thyroid peroxidase. In order to locate the in vivo site of iodination, the initial cytochemical appearance of this enzyme has been determined in fetal rat thyroid and its presence correlated with the onset of iodinated thyroglobulin synthesis. Peroxidase first appears in follicular cells during the 18th day of gestation. It is seen first in the perinuclear cisternae, the cisternae of the endoplasmic reticulum, and within the inner few Golgi lamellae. These organelles presumably represent sites of peroxidase synthesis. During the 19th and 20th days of gestation, there is a tremendous increase in peroxidase activity. In addition to the stained sites described, there are now many peroxidase-positive apical vesicles in the follicular cells. Newly forming follicles stain most conspicuously for peroxidase, the reaction product being heavily concentrated at the external surfaces of apical microvilli and in the adjacent colloid. Iodinated thyroglobulin becomes biochemically detectable in thyroids during the 19th day of gestation and increases greatly during the 20th day. The parallel rise in peroxidase staining that just precedes, and overlaps, the rise in iodinated thyroglobulin, suggests that apical vesicles and the apical cell membrane are the major sites of iodination within the thyroid follicle.